Formação de professores na perspectiva da Complexidade: um estado da arte - Farias, Priscila Moreira Silva de (2020)
The present study is the result of the concerns experienced in the course of my professional trajectory and intends on Teacher Education from the perspective of Complexity, with a look at continuing education. From the questions: Can the perspective of Complexity be considered a possibility for teacher training in and for contemporary times? What do academic productions reveal about this relationship? What does the research on continuing teacher education say in this perspective? The following objectives were chosen: to build the state of the art from theses and dissertations that link teacher training and Complexity; analyze what academic productions reveal about this relationship; identify in which contexts the academic productions were developed, which subjects take the focus of investigation, which are the methodological choices and the results achieved in each research, also identifying what the studies bring about the continuing education of teachers in Complexity, understanding as such This approach presents itself as a possibility for the field of teacher education in and for contemporary times. To carry out the study, a theoretical framework was built based on authors such as Khun (1982), Santos (1998), Capra (1996, 2005, 2006), Morin (1991, 1998, 2001, 2004, 2007), André (2011), Behrens (1999,2005, 2006, 2007, 2011), Candau (1997), Imbernón (2011), Nóvoa (1992, 1995, 2017) among others. Initially, the discussion about the term paradigm was presented, understanding it as a set of beliefs that subsidize our way of thinking and operating at a certain moment. The strengthening of the Newtonian-Cartesian paradigm was emphasized with its fragmentation and reductionist vision in the area of education and in the field of Teacher Education. A new perspective was proposed: Complexity, which shows itself as a possibility for the educational scenario and teacher training at the present time and reflected on the relationship between continuing teacher education and Complexity. Supported by a qualitative approach, the research had a bibliographic character and used the academic productions available in the databases of Google Scholar and the Digital Library of Theses and Dissertations in the construction of the state of the art. The findings totaled 20 papers, including theses and dissertations within a time frame from 2000 to 2018. The results obtained showed that the south and southeast regions and private institutions concentrate the largest number of works. They also pointed out that there is a predominance of qualitative research in the studies analyzed and referring to the subjects taken as the focus of investigation, the teacher is identified and the courses and tools that form it. Complexity has proved to be fruitful in the field of Teacher Education today and although it is still an incipient field, there are already consolidated productions that deal with the theme in different dimensions of work, namely, in initial and continuing education, in the final years of Elementary School, in High School, Higher Education, Post-Graduation at the Specialization level and in the technological and professional dimensions. Regarding continuing education, understood as professional teacher development, it was found that Complexity can be reflected in it, which accompanies the need for teachers to seek training throughout their professional career.